PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADAPERUSAHAAN FARMASI YANG TERDAFTAR DI BEI - Violiandani, Erine; Wahyuni, Ika; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Pharmaceutical companies are companies whose production focuses on medicines and health The value of a company can basically be measured in several ways, one of which is the company's stock price. The purpose of this study was to determine the significance of the effect of Liquidity and Profitability on Firm Value of Dividend Policy. This research uses descriptive and quantitative research The population in this study are 12 pharmaceutical sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period The sampling technique in this study used a purposive sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Liquidity has a negative but significant effect on Dividend Policy, Profitability has a positive but not significant effect on Dividend Policy, Liquidity has a significant positive effect on Company Value, Profitability has a significant positive effect on Company Value, Profitability has an effect positive but not significant to company value. The results of the indirect influence hypothesis test show that the variable Liquidity on Dividend Policy through Company Value has a positive but not significant effect, Profitability on Dividend Policy through Company Value has a negative but not significant effect.